Gender Representation in EFL/ESL Textbooks in Indonesia: A Literature Review - Pebrina Nurwahyuningsih; Nurianti Nurianti; Nurlinda Nurlinda (Hasanuddin University, 2023)
Gender studies on language education have been a concerning topic among scholars. It has been encouraged through some interest in international organizations and Indonesia's government regulation on gender equality. However, few studies have investigated the review of gender representation in English textbooks in Indonesia. To fill this gap, the present study aims to review and discuss the studies of gender representation in learning materials, mainly English textbooks in Indonesia, and the possible future direction of the studies related to be conducted. The study was conducted through the literature analysis that was published within the last five years. The literature analysis involved gender representation in English textbooks in Indonesia, both junior and senior high school level textbooks. The first part of the paper presents an illustration of gender history in Indonesia. The second part discusses the current studies of gender representation in English textbooks in Indonesia. The third part attempts to explain the possible future of the studies related to be conducted. The study concludes that textbook plays an important role as a media that constructs both students' and teachers' perspectives on gender value and awareness in society and culture. Suggestions for further studies are made to bring other directions in conducting gender studies in English textbooks in Indonesia.